2019
DOI: 10.3949/ccjm.86a.18130
|View full text |Cite
|
Sign up to set email alerts
|

Women’s health 2019: Osteoporosis, breast cancer, contraception, and hormone therapy

Abstract: K eeping up with current evidence-based healthcare practices is key to providing good clinical care to patients. This review presents 5 vignettes that highlight key issues in women's health: osteoporosis screening, hormonal contraceptive interactions with antibiotics, hormone replacement therapy in carriers of the BRCA1 gene mutation, risks associated with hormonal contraception, and breast cancer diagnosis using digital tomosynthesis in addition to digital mammography. Supporting articles, all published in 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…However, recent evidence showed that estrogen-alone therapy was not associated with any increase in mortality 19 or in the risk of breast cancer, even in the women who carry the BRCA1 gene mutation. 20 We need to remember that, in females who carry the BRCA1 mutation, the cumulative risk of ovarian and breast cancer by age 80 is over 40 and 70%, respectively. 21 Prophylactic salpingo-oophorectomy is currently the only strategy able to reduce the risk of both cancers.…”
Section: Hormonal Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent evidence showed that estrogen-alone therapy was not associated with any increase in mortality 19 or in the risk of breast cancer, even in the women who carry the BRCA1 gene mutation. 20 We need to remember that, in females who carry the BRCA1 mutation, the cumulative risk of ovarian and breast cancer by age 80 is over 40 and 70%, respectively. 21 Prophylactic salpingo-oophorectomy is currently the only strategy able to reduce the risk of both cancers.…”
Section: Hormonal Therapymentioning
confidence: 99%
“…Unfortunately, the premature withdrawal of ovarian hormones induced by this surgery causes long-term AEs that can be avoided, or at least limited, with HRT without a significant increase in cancer incidence. 14,20 For this reason, there is now a large scientific consensus that hormonal therapy at menopause represents an effective prevention strategy for osteoporosis and fragility fractures, with an overall favorable benefit to risk ratio when it is started before 60 years of age and within 10 years from the last menses. 15 The hormonal options available for the treatment and prevention of postmenopausal bone loss are HRT, tibolone, and SERMs.…”
Section: Hormonal Therapymentioning
confidence: 99%